2020
DOI: 10.1111/srt.12908
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of the anatomical changes in the scalp and hair follicles in androgenetic alopecia using magnetic resonance imaging

Abstract: Background Although the structural changes of the scalp in androgenetic alopecia (AGA) have been reported, these changes have been poorly understood. It is expected that modern MRI would visualize the scalp anatomy in vivo. This study aimed to explore whether AGA causes (a) changes in the thickness of the scalp, (b) anatomical changes in the hair follicles, and (c) changes in the signal intensity of MRI. Materials and Methods Twenty‐seven volunteers underwent MRI for hair and scalp (MRH) and were categorized i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…A previous study reported the pathological and imaging findings of AGA, revealing that patients with AGA had reduced scalp thickness and thinner subcutaneous tissue layer compared with healthy controls. 22 Our findings were consistent with the previous results. At the vertex, the subcutaneous tissue layer was not statistically significantly different in patients with severe alopecia areata compared with healthy volunteers.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…A previous study reported the pathological and imaging findings of AGA, revealing that patients with AGA had reduced scalp thickness and thinner subcutaneous tissue layer compared with healthy controls. 22 Our findings were consistent with the previous results. At the vertex, the subcutaneous tissue layer was not statistically significantly different in patients with severe alopecia areata compared with healthy volunteers.…”
Section: Discussionsupporting
confidence: 94%
“…We found that the scalp and subcutaneous layer were thinner than healthy volunteers in patients with tertiary AGA at the vertex. A previous study reported the pathological and imaging findings of AGA, revealing that patients with AGA had reduced scalp thickness and thinner subcutaneous tissue layer compared with healthy controls 22 . Our findings were consistent with the previous results.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, recent reports demonstrated the utility of MRI in evaluating dermatofibrosarcoma tumors 27 as with tumors mentioned above in this paragraph MRI was useful in designing a surgical excision and in differentiating between this tumor and other lesions. 27 New skin/skin related MRI diagnostic applications include MRI evaluation of scalp alopecia 28,29 (primary use is to evaluate effectiveness of new therapies-see MRS discussion below), abnormal brain MRI findings in patients with atopic deramtitis 30 and use of brain functional MRI to evaluate changes induced by skin pricking/itch/pain sensation. 31,32 In the field of skin MRS no new studies appeared recently.…”
Section: New Mri/mrs Applicationsmentioning
confidence: 99%
“…Magnetic resonance imaging had been utilized to noninvasively analyze anatomical changes in the scalp and hair follicles in androgenetic alopecia and alopecia areata. 6,7 A previous study sought to construct a facial map based on six biophysical parameters in 20 volunteers, aged 24−83 years. 1 When the participants were divided into groups with mean ages in their 30s and 70s, the younger group displayed significantly higher TEWL and stratum corneum hydration, while exhibiting lower pH levels.…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing research efforts have attempted to elucidate age‐related variations in noninvasive parameters. Magnetic resonance imaging had been utilized to noninvasively analyze anatomical changes in the scalp and hair follicles in androgenetic alopecia and alopecia areata 6,7 . A previous study sought to construct a facial map based on six biophysical parameters in 20 volunteers, aged 24−83 years 1 .…”
Section: Introductionmentioning
confidence: 99%